2022
DOI: 10.3390/healthcare10071233
|View full text |Cite
|
Sign up to set email alerts
|

Implementation and Evaluation of Two Nudges in a Hospital’s Electronic Prescribing System to Optimise Cost-Effective Prescribing

Abstract: Providing healthcare workers with cost information about the medications they prescribe can influence their decisions. The current study aimed to analyse the impact of two nudges that presented cost information to prescribers through a hospital’s electronic prescribing system. The nudges were co-created by the research team: four behavioural scientists and the lead hospital pharmacist. The nudges were rolled out sequentially. The first nudge provided simple cost information (percentage cost-difference between … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 30 publications
(29 reference statements)
0
4
0
Order By: Relevance
“…Other studies have found that having a preselected or “defaulted‐on” order has been shown to effect change 22 . Finally, alternative interventions to influence medication prescribing, such as showing cost information or cost savings, 23 have been equally unsuccessful at changing clinician behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have found that having a preselected or “defaulted‐on” order has been shown to effect change 22 . Finally, alternative interventions to influence medication prescribing, such as showing cost information or cost savings, 23 have been equally unsuccessful at changing clinician behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies focusing on medications focus on medication deprescribing or medication reconciliation, as opposed to encouraging clinicians to add a medication 7 20–23. Finally, alternative interventions to influence medication prescribing, such as showing cost information or cost savings,8 have been unsuccessful at changing clinician behaviour. Laboratory test ordering is a straightforward outcome (ordered vs not), whereas medication ordering for analgesia then requires administration as well as better pain management and finally, opioid reduction.…”
Section: Discussionmentioning
confidence: 99%
“…Open access other interventions to improve patient care. [6][7][8][9] However, clinical decision support can add complexity and workflow tasks that contribute to clinician burn-out, and it needs to be justified in terms of clinical benefit. In a previous study, 10 we tested whether requiring an active choice for NSAID ordering (a 'hard stop') in the pain management order panel in our standard admission order set changed NSAID prescribing, but we found this approach to be ineffective.…”
Section: What This Study Addsmentioning
confidence: 99%
See 1 more Smart Citation